Aboriginal justice and the Charter : realizing a culturally sensitive interpretation of legal rights - Milward, David Leo, 1974- (Law and society series., 2012)
"How can Aboriginal justice be practically implemented in ways that go beyond sentencing initiatives and parallels to restorative justice? Aboriginal Justice and the Charter explores the tension between Aboriginal justice methods and the Canadian Charter of Rights and Freedoms, seeking practical ways to implement Aboriginal justice. David Milward examines nine legal rights guaranteed by the Charter and undertakes a thorough search for interpretations sensitive to Aboriginal culture. Milward strikes out into new territory well beyond that charted by the Royal Commission on Aboriginal Peoples in the mid-1990s. He examines why Aboriginal communities seek to explore different paths in this area and identifies some of the applicable constitutional constraints. This book considers a number of specific areas of the criminal justice process in which Aboriginal communities may wish to adopt different approaches, tests these approaches against constitutional imperatives, and offers practical proposals for reconciling the various matters at stake. Milward grapples with the difficult question of how Aboriginal justice systems can be fair to victims, offenders, and the community while at the same time complying with the protections guaranteed to all Canadians by the Charter"--Provided by publisher